(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Literary works serve as vessels for conveying cultural values, ideas, and attitudes, illuminating the customs and beliefs of various societies. Across the globe, a multitude of diverse cultures coexist, each reflecting an array of perspectives and convictions. Through their writings, authors not only express their personal viewpoints but also introduce readers to the richness of cultural diversity. Cultural values are often articulated through the author’s narrative voice. Among the many themes explored in literature, food has captured the attention of scholars from fields such as economics, human rights, ethics, sociology, anthropology, and literature itself. Numerous studies have been conducted to investigate the pivotal role of food in the human experience. Within literary texts, food frequently serves as a lens through which cultural differences are examined and understood. Anita Desai’s novel Fasting, Feasting abounds with metaphorical references to food and its consumption. The novel’s title itself evokes the concept of consumption, delving into how characters relate to food as a means of highlighting inequalities—who indulges in abundance and who endures deprivation. This study centers on the narrative strategies that employ culinary motifs, including metaphors, symbols, and representations, to explore their intricate ties to identity and culture.